Salinity stress endurance of the plants with the aid of bacterial genes - Zamanzadeh-Nasrabadi, Seyyedeh Maryam; Mohammadiapanah, Fatemeh; Hosseini-Mazinani, Mehdi; Sarikhan, Sajjad (Frontiers in Genetics, 2023)
The application of plant growth-promoting bacteria (PGPB) is vital for sustainable agriculture with continuous world population growth and an increase in soil salinity. Salinity is one of the severe abiotic stresses which lessens the productivity of agricultural lands. PGPB are key players in solving this problem and can mitigate salinity stress. The highest of reported halotolerant PGPB belonged to Firmicutes (approximately 50%), Proteobacteria (40%), and Actinobacteria (10%), respectively. The most dominant genera of halotolerant PGPB are Bacillus and Pseudomonas. Currently, the identification of new PGPB with special beneficial properties is increasingly needed. Moreover, for the effective use of PGPB in agriculture, the unknown molecular aspects of their function and interaction with plants must be defined. Omics and meta-omics studies can unreveal these unknown genes and pathways. However, more accurate omics studies need a detailed understanding of so far known molecular mechanisms of plant stress protection by PGPB. In this review, the molecular basis of salinity stress mitigation by PGPB is presented, the identified genes in the genomes of 20 halotolerant PGPB are assessed, and the prevalence of their involved genes is highlighted. The genes related to the synthesis of indole acetic acid (IAA) (70%), siderophores (60%), osmoprotectants (80%), chaperons (40%), 1-aminocyclopropane-1-carboxylate (ACC) deaminase (50%), and antioxidants (50%), phosphate solubilization (60%), and ion homeostasis (80%) were the most common detected genes in the genomes of evaluated halotolerant plant growth-promoting and salinity stress-alleviating bacteria. The most prevalent genes can be applied as candidates for designing molecular markers for screening of new halotolerant PGPB.